WAIS Divide WDC06A Nitrate Isotope Record - Buffen, Aron; Hastings, Meredith (IEDA: US Antarctic Program Data Center, 2017)
This dataset contains nitrate concentration and isotopic composition (d15N, d18O, D17O) measurements on the WAIS Divide WDC06A ice core.